Generation of stably expressing IRF5 spliced isoform in Jurkat cells - Ashwinder Kaur; Chee-Mun Fang (Progress in Microbes and Molecular Biology)
Lentiviral transduction enables the generation of gain-of-function of a targeted gene in mammalian cells. Single-cell cloning through limiting dilution can establish a population of cells with homogenous transgene expression for exploring protein function. Here, we describe step by step optimized protocols for generating clonal stably expressing using crude lentiviral supernatant in Jurkat cells. Although the protocol is for general use, we will detail how to create stable cell lines based on Jurkat cells expressing IRF5 spliced isoform. These protocols will be broadly useful for researchers seeking to apply overexpression by viral transduction and generation of stable clone to study gene function in mammalian cells.